Towards the ontology-based approach for factual information matching - Sharonova, Natalia Valeriyevna; Doroshenko, Anastsiia; Cherednichenko, Olga (Друкарня Мадрид, 2018)
Factual information is information based on facts or relating to facts. The reliability of automatically extracted facts is the main problem of processing factual information. The fact retrieval system remains one of the most effective tools for identifying the information for decision-making. In this work, we explore how can natural language processing methods and problem domain ontology help to check contradictions and mismatches in facts automatically.
Keywords: fact; natural language processing; information extraction; ontology; reference model; software